197k views
3 votes

y'= (1)/(6) x(1- y^(2) )

This equation has the 2 constant solutions (in increasing order), y=? and y=?
The solution of this equation subject to the initial condition y(0)=7y(0)=7 is ?

1 Answer

4 votes

(\mathrm dy)/(\mathrm dx)=\frac16x(1-y^2)

\displaystyle\int(\mathrm dy)/(1-y^2)=\frac16\int x\,\mathrm dx

\frac12\ln|1+y|-\frac12\ln|1-y|=\frac1{12}x^2+C

\ln\left|(1+y)/(1-y)\right|=\frac16x^2+C

(1+y)/(1-y)=e^(x^2/6+C)

-1+\frac2{1-y}=Ce^(x^2/6)

y=1-\frac2{1+Ce^(x^2/6)}

Given that
y(0)=7, we get


7=1-\frac2{1+Ce^0}\implies C=-\frac43

so the particular solution is


y=1-\frac2{1-\frac43e^(x^2/6)}
User Junghyun
by
6.2k points